1997
DOI: 10.1007/bf02505324
|View full text |Cite
|
Sign up to set email alerts
|

Survival and quality of life after percutaneous nephrostomy for malignant ureteric obstruction in patients with terminal cervical cancer

Abstract: We describe 24 consecutive patients with cervical cancer stage III or IV who received palliative urinary diversion by percutaneous nephrostomy. All patients had proven malignant ureteric obstruction, uremia and failed ureteric stenting. 11 of 17 patients with extensive primary cancer and local lymph node involvement had an acceptable quality of life for 2 or more months while the mean survival was 5.6 months. Patients with disseminated metastasizing cancer were not satisfactorily served by nephrostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
0
31
0
3
Order By: Relevance
“…This retrospective study revealed that in this cohort of patients, predominantly locally advancing pelvic malignancies gave 6,7 months. These series, however, included patients with benign ureteric obstruction 6 and gynaecological malignancy, 5,7 which we suggest perform more favourably than other pelvic malignancies.…”
Section: Discussionmentioning
confidence: 67%
“…This retrospective study revealed that in this cohort of patients, predominantly locally advancing pelvic malignancies gave 6,7 months. These series, however, included patients with benign ureteric obstruction 6 and gynaecological malignancy, 5,7 which we suggest perform more favourably than other pelvic malignancies.…”
Section: Discussionmentioning
confidence: 67%
“…18 Conversely, patients with cervical carcinoma who had disseminated metastasis did poorly. 14 The majority of our patients had disseminated disease at the time of diversion. In patients with pelvic tumors, the performance status was significantly better in those with locally advanced (including lymph node metastasis) disease compared with those with disseminated disease (P ϭ 0.03); however, no statistically significant survival benefit was noted.…”
Section: Discussionmentioning
confidence: 79%
“…In a few studies on palliative urinary diversion in patients with advanced malignancies, the impact on quality of life after diversion has been addressed. 5,13,14 Most of these studies were conducted prior to the routine use of endoscopic diversion. The assessment of quality of life is difficult, and different arbitrary definitions have been used.…”
Section: Discussionmentioning
confidence: 99%
“…The nephrostomy catheter can be inserted into the dilated renal pelvis in local anesthesia [14] . Patients' acceptance of permanent nephrostomy is low.…”
Section: Discussionmentioning
confidence: 99%